Profile of Melanoma and Non-Melanoma Skin Cancer based on Histopathology Results - Zulfa, Fathimah; Windarti, Indri; Sutarto; Carolia, Novita (Medula, 2024)
Skin cancer is an abnormal condition in the structure of the skin that arises because the skin loses the ability to regenerate periodically. Skin cancer is high risk in people who live in tropical countries such as Indonesia. All provinces in Indonesia receive evenly distributed sunlight including Lampung province. Lampung Province is an agricultural province with the dominance of the population working in agriculture and marine sectors. Agriculture and marine sectors workers get continuous and long-term exposure to UV rays so that they are at high risk of skin disorders, one of them is skin cancer. This study was conducted in August-December 2024 in the medical record from Dr. H. Abdul Moeloek Hospital Bandar Lampung. This study was observational and was conducted by collecting data and univariate analysis on medical record data of skin cancer patients including the type of skin cancer, age, gender ], and location of tumor growth of skin cancer patients. The results showed that the most common type of skin cancer diagnosed at Dr. H. Abdul Moeloek Bandar Lampung Hospital in the 2019-2024 period was non-melanoma skin cancer (squamous cell carcinoma followed by basal cell carcinoma). The most common age of skin cancer patients is ≥40 years old, female and the location of tumor growth is mostly in the head and neck area.